Phosphorus use efficiency in conservation agricultural system: impact of organic restitution - Eberhardt, Diogo Néia (2013)
The tropical savannas cover an area of approximately 1,900 million ha second biome of Brazil. Phosphorus (P) is frequently a major or even the prime limiting factor for plant growth in the subtropical and tropical regions (highly weathered soils). Small-scale farming systems are fairly representative in Brazil, accounting for approximately 84.4% of Brazilian agriculture establishments and the conventional tillage being the common practice in the systems. The objective of this work was to study the dynamics of P in an agronomic experiment located in the Cerrado region, on the efficient use of P in conservation agricultural system: i) assessing soil spatial fertility variability of P, Ca, Mg, K and pH; ii) the C and P stock; and iii) characterizing of species of P by 31P-NMR spectroscopy. The area of study is located at Cerrado biome (Brazilian neotropical savannas) in a clayey Oxisol classified as Haplic Ferralsol. The treatments are characterized by different agricultural practices (conventional tillage - CT; and no-tillage - NT), and the presence or not of cover crops (Brachiaria ruziziensis - a grass specie and Cajanus cajan - a leguminous specie) with maize (Zea mays). In the study of spatial variability the data were analyzed by descriptive statistics and geostatistics. The semivariograms were computed according to the spherical model for pH H2O, pH CaCl2, K, LogK, Ca and Mg. P and LogP were modeled using a nugget effect model. Even ~20 years after deforestation the spatial distribution of pH H2O, pH CaCl2, Ca, Mg and exchangeable K is influenced by the wood windrow burning that took place during deforestation. The spatial distribution of P was not affected by the windrow woods burning. In the study conducted to improve the understanding of the conservation agriculture impact in small-scale farming systems on soil C and P stocks in the 0-40 cm layer due to its importance in agrosystem management. The C stocks (up to 40 cm depth) in NT and MCr treatments were significantly superior. The P stocks varied between 0.63 and 0.91 t ha-1 and were not significantly different among the treatments. No-till treatment and MCr treatments were the only ones that showed gains carbon, where the accumulation was 2.67 and 2.91 t C ha-1 year-1, respectively. The highlight of MCr treatment shows the important role of legumes in carbon sequestering. In the study of soil organic P aiming to determine how the amounts and forms of organic phosphorus vary according to the tillage systems and cover crops used. The Po (PMonoester and PDiester) values determined by NMR were not different among the treatments. The levels of Po were higher than 59% of the total content of POlsen and the main changes in relation to P occurred in the topsoil. The values show that Po does not change (PMonoester and PDiester) among the treatments. The maintenance of the Po levels, no accumulation and loss, suggests that the availability of P is not necessarily linked to accumulation, but to the increase of fluxes between active pools.